From "Crisis" to Imagination : Putting White Heroes Under Erasure Post-George Floyd - Mendes, Ana Cristina (2021)
In the immediate aftermath of George Floyd’s murder on May 25, 2020, global protests against racialized police brutality targeted statues and other public art forms symbolizing racism. Either framed as a “weird global media event” or “global iconic event,” Floyd’s murder forced a reckoning with histories of oppression and systemic racism, with a potential enduring social effect and a transnational historical significance by inviting resonance and global solidarity. This article focuses on the U.K. context and spans a decade to invite a rethinking of ideas of crisis, history, and hero through a consideration of the toppling of Edward Colston’s statue and its pushing into the Bristol Harbour on June 7, 2020, by Black Lives Matter (BLM) protesters, and Yinka Shonibare CBE’s artwork Nelson’s Ship in a Bottle (2010–2012), commissioned for the “Fourth Plinth” temporary exhibits in Trafalgar Square. Such consideration bears on this contemporary moment when we are witnessing globally connected protest actions calling for the decolonization of public material culture.